Penggunaan Komputer Untuk Pembelajaran Matematika - Abdussakir, Abdussakir (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
Today, many schools have computer. Nevertheless, school uses computer forÂ extracurricular, practicum, and even just for â€œdecorationâ€. The computerÂ has not been used maximally in the learning of mathematics. Whereas,Â various research have shown that the result of computer using in theÂ learning mathematic better than without computer.Keywords: Computer, Using, Learning, Mathematics.